Sustained Release of Nitric Oxide and Cascade Generation of Reactive Nitrogen/Oxygen Species via an Injectable Hydrogel for Tumor Synergistic Therapy - Wang, Yaoben; Yang, Xiaowei; Chen, Xiaobin; Wang, Xin; Wang, Yang; Wang, Hancheng; Chen, Zhiyong; Cao, Dinglingge; Yu, Lin; Ding, Jiandong (Advanced functional materials, 2022)
Reactive nitrogen species (RNS) generated via the reaction of nitric oxide (NO) with reactive oxygen species (ROS) are more lethal than ROS, and thus RNS‐mediated therapy has great potential in cancer treatment, yet it is still largely unexploited. Herein, a novel, injectable and NO‐releasing hydrogel (NO‐Gel) composed of α‐(nitrate ester) acetic acid‐modified amphiphilic copolymers is developed. To further convert released NO to RNS, glutathione (GSH)‐sensitive CuCys nanoparticles (NPs) and β‐lapachone (Lapa) are co‐loaded into the NO‐Gel. This hydrogel system possesses a temperature‐induced sol‐gel transition and can continuously liberate Lapa, CuCys NPs, and NO in vitro for up to 3 weeks. The sustained supply of Lapa can efficiently boost hydrogen peroxide (H2O2) concentration in cancer cells, and intracellular GSH can induce the rapid release of NO and the reduction of CuCys NPs. With elevating H2O2 levels and producing highly reactive Cu(I), the Cu(I)‐catalyzed Fenton‐like reaction is dramatically enhanced, resulting in the generation of abundant hydroxyl radicals (·OH), and the subsequent cascade reactions among ·OH, H2O2, and NO cause more lethal RNS pool. After a single peritumoral injection of the hydrogel system, the cascade generation of ROS and RNS plus the substantial depletion of GSH can significantly suppress tumor growth. An injectable thermosensitive hydrogel with inherent long‐acting NO‐releasing capacity (NO‐Gel) is developed. After loading β‐lapachone and CuCys nanoparticles into the NO‐Gel, the hydrogel system (Lapa/CuCys@NO‐Gel) can elevate intracellular reactive oxygen species and reactive nitrogen species levels and deplete glutathione through cascade reactions. A synergistic antitumor efficacy is achieved after a single peritumoral injection of the hydrogel system.